Experimental study on impact failure characteristics of deep circular roadway - Shoujian PENG; Yan YANG; Jiang XU; Qingfeng XU; Chaolong QIN; Xiaoli NONG (Meikuang Anquan)
In order to study the impact failure characteristics of deep circular roadway under the condition of disturbance load, based on the self-developed multi-functional physical simulation test system of rock burst, the impact failure test of circular roadway was carried out for large-scale rock-like materials. The impact failure process of underground 800 m roadway under mining disturbance was simulated, and the stress-strain, blasting, acoustic emission and infrared radiation response characteristics of impact failure of deep circular roadway were analyzed. The results show that the impact failure process of deep circular roadway is divided into four stages: quiet period, particle ejection period, block spalling period and comprehensive failure period. After the failure of the roadway, “V” shaped blasting pits are formed on both sides. The area of the right blasting pit is larger than that of the left, and the degree of damage is higher than that of the left. When the roadway began to produce particle ejection, it entered the initial failure stage, the acoustic emission count and energy increased slowly, the temperature of the infrared radiation temperature field was evenly distributed, and the degree of differentiation was low. With the increase of disturbance stress, the energy of acoustic emission count increases gradually, the temperature field of infrared radiation rises and forms a high temperature concentration area, and the temperature field differentiation is obvious. The acoustic emission count and energy increase suddenly near comprehensive damage, the degree of infrared radiation temperature field differentiation reaches the maximum and then decreases, and the overall temperature of the temperature field in the low temperature region increases.